Fooled by the Film: Delayed Diagnosis of Incarcerated Small-Bowel Hernia After Laparoscopic Surgery for Endometrial Cancer. (1st February 2012) - Rosenthal, Adam N.; Heron, Gary; Widschwendter, Martin; Read, Samantha; Brunell, Carol; Mould, Tim A.
Abstract : Abstract: Prompt recognition of laparoscopic surgical complications is vital. We present a case highlighting the dangers of relying on plain radiography for exclusion of bowel herniation through a port site. Early recourse to cross-sectional imaging is recommended to avoid such pitfalls.